Soil organic matter characterization in rubber based systems in central Kerala - A spectroscopic approach - Philip, Annie; Abraham, Joshua (Journal of Plantation Crops, 2020)
Land use and agro-management practices influence the quantity and quality of soil organic matter. Soil properties to a large extent are influenced by the content and nature of soil organic matter. A field study was conducted in two locations, one at Amayannoor and the other at Mundakayam in Kottayam district, Kerala to undertake the spectroscopic characterization of soil organic matter. The four rubber systems investigated at Amayannoor were mature rubber, immature rubber with cover crop Pueraria phaseoloides, immature rubber with inter-crop banana and immature rubber with inter crop pineapple. At Mundakayam, mature rubber, immature rubber with cover crop Mucuna bracteata, immature rubber with inter crop banana, and immature rubber with inter crop pineapple were investigated. Both, UV-Vis and FTIR spectroscopic studies were carried out. Soil organic matter under mature rubber was observed to be more aromatic than soil under immature systems at both locations. Among the different immature systems, the soil organic matter in rubber-Pueraria system showed the presence of more carbohydrates and polysaccharides than rubber-pineapple and rubber-banana systems. However, rubber-Mucuna system showed relatively higher aromaticity than rubber-pineapple and rubber-banana systems. This study confirms the earlier reports about the faster decomposition of soil organic matter in rubber-Pueraria system and slower decomposition of soil organic matter in mature rubber plantation. This spectral investigation also revealed the specific nature viz., higher aromaticity of the soil organic matter in rubber-Mucuna system which contributed towards the buildup of soil carbon in the system.